Aproximación a la racialidad en un género musical: la zarzuela - Burunate Sánchez, Teresa Victoria (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The existence of racial discriminatory forms visible or non-visible which have survived from colonial epoch the pass of time, preserving the legacy of colonial discriminatory hegemony in social imaginary, is recognized in our country nowadays, it has been included as leading topic in Radio and TV programs but no with the strength that racial problem required in order to become theme of the needed the debate where actions and effective strategies will be stated free of colonial thoughts. Using the proper international environment framework created by The United Nations’ declaration of 2015 year. It is necessary to know and spread what support racism survive now that’s possible achieve by reading, shearing experiences, researching, acquiring knowledge that allows to recognize the new adopted appearances and how it is reproduced at social psychological level, maintaining the fear to negro as a result of wrong cultural vision of him. That’s why the objective of the present paper is to find out how the Negro has been represented and what the psychological and social consequences of exclusion are carried by two female characters of a well-known lyric piece in a specific musical gender: la zarzuela.